Chunking Strategy; in Enhancing Fourth Semester Students’ Reading Skill at English Department of Muhammadiyah University - HJ Wahid, Jusmin; A. Thais, Iswan (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2020)
Teaching reading skill to the students needs applying the appropriate strategy to stimulate studentsâ€™ understanding to meet the main purpose in the teaching and learning process. It was expected that the strategy itself should be able to be used by the teacher to design the better ways for the students in order to acquire important information. It is realized that many students now need as much information as possible in comprehending all the texts they read. To overcome this problem, the researcher used chunking strategy to improve studentsâ€™ reading skill. The researcher used true experiment to design this research, then the pre-test was used to find out whether this group in the same level and the post-test was used to detect the progress of the students. The total numbers of the students who involved in the pre-test and post-test were 20. The data showed that the information in the post-test that;Â mean score was 70.50, and the pre-test got score was 61.85 then the standard deviation in the post-test was 10.32 and the standard deviation in pre-test is 8.27. It could be concluded that the students get significant progress in their understanding of reading skill by using Chunking strategy in English Department.